A Qualitative Study on Practice and Awareness of Teachers Continuous Professional Development in Primary schools of Aleta Wondo town, Sidama/Ethiopia - Milkiyas Asso; Ashagre Alito (Peerian Journals Publishing, 2024)
This study examined the practice and awareness of teachers CPD in primary schools of Aleta Wondo town. A qualitative research method was employed. The study was guided by three research questions. Interview and document analysis were used as the data gathering tools of this study. The data gathered through interviews and document analysis were analyzed via thematic description. The findings indicate that the primary school teachers in the sampled schools have good awareness on CPD practice. On the other hand, the findings of the study showed that the extent of teachers CPD practices was at moderate level. The study also found that heavy workload, time, and school factors are associated factors that affect teachers’ practice in CPD activities. Thus, this study recommends that the zone and woreda education sectors in collaboration should hire additional teachers to reduce teachers’ workload in order to let them to have much time to study effectively the CPD activities. The school principals try to create reward mechanisms and continually convince teachers about CPD advantages in order to sustain interest and commitment of teachers in the CPD practice
Keywords: CPD; Awareness; Practice